2015
DOI: 10.1152/ajplung.00098.2015
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal in vivo microcomputed tomography of mouse lungs: No evidence for radiotoxicity

Abstract: Before microcomputed tomography (micro-CT) can be exploited to its full potential for longitudinal monitoring of transgenic and experimental mouse models of lung diseases, radiotoxic side effects such as inflammation or fibrosis must be considered. We evaluated dose and potential radiotoxicity to the lungs for long-term respiratory-gated high-resolution micro-CT protocols. Free-breathing C57Bl/6 mice underwent four different retrospectively respiratory gated micro-CT imaging schedules of repeated scans during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 45 publications
3
51
0
Order By: Relevance
“…26,39 Retrospective respiratory gating resulted in four data sets per scan, corresponding to different phases of the breathing cycle. The data set obtained during the end expiratory phase of the breathing was used for further analysis.…”
Section: Image Analysismentioning
confidence: 99%
“…26,39 Retrospective respiratory gating resulted in four data sets per scan, corresponding to different phases of the breathing cycle. The data set obtained during the end expiratory phase of the breathing was used for further analysis.…”
Section: Image Analysismentioning
confidence: 99%
“…; Vande Velde et al . ). The average radiation dose during medical μCT studies on mice falls in the range of 0·02–0·96 Gy (Table ), far below their LD 50(30) of 5–7·6 Gy (Taschereau, Chow & Chatziioannou ).…”
Section: Discussionmentioning
confidence: 97%
“…Although caution is required when high radiation doses are being used (Vande Velde et al . ), a cumulative radiation dose of ≈5 Gy appears to have no significant negative effects on tissues in mice (Detombe et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…They predicted that for a whole body scan, the dose could vary between 80 and 133 mGy. Recently, Vande Velde et al [33], using a SkyScan Bruker microCT scanner (parameters: 50 kVp and 120 ms; 50 kVp and 450 ms) and adult mice, reported absence of radiation induced lung damage even at a high dose protocol of 450 ms, despite measured skin doses as high as 1,104 mGy and lung doses of 813 mGy. They suggested that high dose microCT is safe for longitudinal lung studies, but recognized the current limited understanding among the scientific community on the impact of high absorbed doses in small animal longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%